Diffusion Monte Carlo studies of isotope-substituted water trimers - Sorenson, J; Gregory, J; Clary, D (1996)
We report the ground-state properties of several partially deuterated water trimers calculated with the rigid-body diffusion Monte Carlo method. Rotational constants are compared with recent experiments and good agreement is found. Tunneling splittings for the hydrogen flip in (HDO)3 are predicted. New results are predicted for the experimentally unexamined mixed trimers.